The cellular pathways and potential therapeutics of Polycystic Kidney Disease. (30th June 2021) - Richards, Taylor; Modarage, Kavindiya; Malik, Soniya A.; Goggolidou, Paraskevi
Abstract : Polycystic Kidney Disease (PKD) refers to a group of disorders, driven by the formation of cysts in renal tubular cells and is currently one of the leading causes of end-stage renal disease. The range of symptoms observed in PKD is due to mutations in cilia-localising genes, resulting in changes in cellular signalling. As such, compounds that are currently in preclinical and clinical trials target some of these signalling pathways that are dysregulated in PKD. In this review, we highlight these pathways including cAMP, EGF and AMPK signalling and drugs that target them and may show promise in lessening the disease burden of PKD patients. At present, tolvaptan is the only approved therapy for ADPKD, however, it carries several adverse side effects whilst comparatively, no pharmacological drug is approved for ARPKD treatment. Aside from this, drugs that have been the subject of multiple clinical trials such as metformin, which targets AMPK signalling and somatostatins, which target cAMP signalling have shown great promise in reducing cyst formation and cellular proliferation. This review also discusses other potential and novel targets that can be used for future interventions, such as β-catenin and TAZ, where research has shown that a reduction in the overexpression of these signalling components results in amelioration of disease phenotype. Thus, it becomes apparent that well-designed preclinical investigations and future clinical trials into these pathways and other potential signalling targets are crucial in bettering disease prognosis for PKD patients and could lead to personalised therapy approaches.